CULTURAL JUSTICE, BASIC INCOME AND THE CAPABILITY APPROACH - YAMAMORI, TORU (Society Register, 2021)
In this paper, we elaborate on a theory of an evolutionary political economy capable of accommodating the issue of cultural justice by taking seriously the redistribution–recognition dilemma, a normative analysis of which has been put forth by Nancy Fraser. While accepting Fraser’s articulation of the dilemma, we resist her concluding that Sen’s capability approach is insensitive to cultural justice or the recognition of difference. There is no automatic guarantee, yet an intermediate theory of recognition or cultural justice could in theory be brought to bear on what is, after all, ‘a framework’. We argue that Fraser’s analysis is well suited to be such an intermediate theory, and propose a theoretical device for an evolutional perspective on redistribution and recognition. We concentrate on identifying the stage of the market process at which policy intervenes to remedy redistribution, and the stage of the communication process at which policy intervenes to remedy recognition. Interventions at the entrance stages of both processes are relatively effective and one possibility for such an intervention is to propose Basic Income, which would make it not inconsistent with the capability approach, even though this approach neither directly suggests such a policy not excludes others.